Correlation of Serum Sodium with Severity of Hepatic Encephalopathy in Liver Cirrhosis Patients Presenting at Tertiary Care Hospital, Lahore - Ali, Aleena; Mahmood, Asad Ullah; Ahmed, Bilal; Gohar, Ali (Biological and Clinical Sciences Research Journal, 2025)
Hepatic encephalopathy (HE) is a serious complication of liver cirrhosis, characterized by cognitive impairment and neurological dysfunction. Emerging evidence suggests that hyponatremia plays a critical role in the pathophysiology of HE, potentially exacerbating its severity. However, the relationship between serum sodium levels and the severity of HE remains an area of ongoing investigation. Objective: To evaluate the correlation between serum sodium levels and the severity of hepatic encephalopathy in cirrhotic patients. Methods: This descriptive cross-sectional study was conducted at the Department of Gastroenterology, Doctors Hospital and Medical Center, Lahore, over a period of six months. A total of 120 patients diagnosed with HE were enrolled using non-probability consecutive sampling. Clinical history, laboratory investigations, and serum sodium levels were documented. The severity of HE was graded using the West Haven classification system. Pearson’s rank correlation test was applied to assess the relationship between serum sodium levels and HE severity, and the Chi-square test was used to evaluate categorical associations. Data analysis was performed using SPSS Version 24, with a p-value of ≤0.05 considered statistically significant. Results: Among the 120 patients, 55 (45.8%) were men and 65 (54.2%) were women, with a mean age of 59.84 ± 7.93 years. Hyponatremia (serum sodium <135 mEq/L) was present in 99 patients (82.5%). A statistically significant inverse correlation was observed between serum sodium levels and the severity of HE (Pearson’s R = -0.285, p = 0.002). Additionally, the Chi-square test confirmed a strong association (p < 0.001) between hyponatremia and HE severity. Conclusion: Hyponatremia is significantly correlated with increased severity of hepatic encephalopathy in cirrhotic patients. Routine monitoring of sodium levels and early corrective interventions may help prevent HE progression and improve patient outcomes. Further research is required to assess the prognostic implications of hyponatremia in HE management.